SOCIALIZATION OF THE IMPORTANCE OF BPJS EMPLOYMENT PROTECTION FOR STUDENTS AND STUDENTS UNDERTAKING INTERNSHIP OR WORK PRACTICE - Indra, I Made (International Journal of Engagement and Empowerment (IJE2), 2025)
The internship or practical work program is a crucial component in education, aiming to provide students with direct experience before entering the professional world. However, students undertaking these activities frequently encounter risks such as work accidents or health issues that can hinder their learning process. Therefore, protection from BPJS Ketenagakerjaan (Workers' Social Security Agency) is essential to guarantee their safety and well-being during these activities. Unfortunately, many students still lack a comprehensive understanding of the benefits and registration procedures for BPJS Ketenagakerjaan. Consequently, this webinar was organized to enhance awareness and provide further understanding of the importance of BPJS Ketenagakerjaan protection for students undergoing internships or practical work. This community service initiative was conducted via an online webinar in the Even Semester of the 2024/2025 Academic Year, specifically in April 2025. The activity, titled "Sosialisasi Pentingnya Perlindungan BPJS Ketenagakerjaan bagi Siswa dan Mahasiswa yang Melaksanakan Magang atau Praktik Kerja" (Socialization on the Importance of BPJS Ketenagakerjaan Protection for Students and University Students Undertaking Internships or Practical Work), was held on Friday, April 11, 2025, from 14.00 - 16.00 WIB, via Zoom Meet. One hundred and five participants attended, including teachers, lecturers, HRD personnel from companies, university students, and high school students. The results indicate a highly positive response, with active engagement during the Q&A session and many participants, suggesting an increased understanding and awareness of the importance of this social security coverage. The program achieved its objective of raising awareness and comprehension regarding BPJS Ketenagakerjaan for interning students.